A Needs Analysis of English for Specific Purposes (ESP) for Business Students in Higher Education - Ulyani, Maya; Anggraini, Retno (Afeksi: Jurnal Penelitian dan Evaluasi Pendidikan, 2025)
This study aims to analyze the learning needs of business students in the context of English for Specific Purposes (ESP) using a qualitative descriptive approach. The participants consisted of 15–20 students from business and professional communication programs who had completed at ESP course. Data were collected through semi-structured interviews, classroom observations, and document analysis. To Analysis the data the resercher used thematic analysis. The findings revealed that needs of ESP students are highly contextual and professionally oriented, with a particular emphasis on speaking and writing skills relevant to business communication such as meetings, presentations, negotiations, and report writing. Major challenges identified include limited technical vocabulary, the use of general materials that lack business relevance, and teacher-centered instruction methods. Students expressed a preference for more authentic, interactive, and task-based learning activities that reflect real-world business practices. The study concludes that ESP learning should adopt communicative and participatory approaches aligned with industry demands to enhance professional competence. The results contribute theoretically to ESP needs analysis and curriculum design, and practically to the development of relevant and effective learning materials for business students.